2003
DOI: 10.1590/s0100-879x2003000600008
|View full text |Cite
|
Sign up to set email alerts
|

The effects of 2,3-diphosphoglycerate, adenosine triphosphate, and glycosylated hemoglobin on the hemoglobin-oxygen affinity of diabetic patients

Abstract: The position of the oxygen dissociation curve (ODC) is modulated by 2,3-diphosphoglycerate (2,3-DPG). Decreases in 2,3-DPG concentration within the red cell shift the curve to the left, whereas increases in concentration cause a shift to the right of the ODC. Some earlier studies on diabetic patients have reported that insulin treatment may reduce the red cell concentrations of 2,3-DPG, causing a shift of the ODC to the left, but the reports are contradictory. Three groups were compared in the present study: 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 26 publications
2
20
0
4
Order By: Relevance
“…Hypertriglyceridemia was also associated with lipase elevation in the univariate analysis, but this association was not significant in the multivariate analysis. It is possible that low phosphate concentrations during DKA might contribute to ischemic tissue injury by lowering red blood cell 2,3-diphosphoglycerate levels, which may be associated with decreased tissue oxygen delivery (10). In two adult studies, hypophosphatemia was also found to be correlated with pancreatic enzyme elevation during DKA (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…Hypertriglyceridemia was also associated with lipase elevation in the univariate analysis, but this association was not significant in the multivariate analysis. It is possible that low phosphate concentrations during DKA might contribute to ischemic tissue injury by lowering red blood cell 2,3-diphosphoglycerate levels, which may be associated with decreased tissue oxygen delivery (10). In two adult studies, hypophosphatemia was also found to be correlated with pancreatic enzyme elevation during DKA (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…HbA1c determines the fasting glucose concentration in diabetic patients and therefore reflects detrimental diabetic complications [52]. HbAlc levels were elevated in T1DM treated with insulin due to poor glycemic control [53].…”
Section: Table 2 Pearson Correlation Test Of Studied Parameters In Cmentioning
confidence: 99%
“…However, it is important to note that HbA1c is neither considered dysfunctional nor harmful. 3 lifetime of the red blood cell, which is approximately 120 days. 4 HbA 1C expressed as a percentage of total blood hemoglobin concentration gives a good retrospective assessment of the mean plasma glucose concentration during the preceding 6-8 weeks while the recent glycemic level has the highest influence and the preceding 30 days contribute only upto 50%.…”
Section: Introductionmentioning
confidence: 99%